Depersonalisation in women providing psychosocial support services - Glomazić, Hajdana (Teorija in praksa, 2025)
The article examines the relationship between depersonalisation and the provision of psychosocial support among women in helping professions. The aim of the study was to determine the extent to which depersonalisation, as a consequence of occupational burnout, is present in women working in these professions, and to identify the factors that predict it. The research was a quantitative empirical cross-sectional study that applied a descriptive/analytical approach. The sample included 302 women from the Western Balkans. The findings show that approximately one-third of the participants exhibited mild symptoms of this phenomenon, whereas 12.5% had moderate to high levels. It was revealed that marital status, holding a professional licence, intercultural training, and international/intercultural experience are predictors of depersonalisation levels.
Keywords: burnout; Delovni stres; depersonalisation; depersonalizacija; gender; helping professions; izgorelost; poklici pomoči; ranljive skupine; secondary traumatisation; sekundarna traumatizacija; Socialno skrbstvo; spol; vulnerable groups